ADAPTASI SOSIAL MAHASISWA ASAL TIDORE DI KELURAHAN TITIWUNGEN SELATAN KOTA MANADO - Ismail, Hasan Basri (HOLISTIK, Journal Of Social and Culture, 2015)
People in Indonesia is a multicultural people, that consist of different culture and tribe, that’s make a human behavior become an important element. This behavior become a social capital to interact with people in their environment. Capability of interact can be affect with people’s existence. With a good interact ability, then he can quickly adapt with each others. The student from Tidore that study in Manado is already stayed in a long time ago. And until now they can easily adapt. The reason is they have a capability to adapt quickly and some factors that can support them to interact is environment factors, historical factors and language factors. The majority of student from Tidore in Manado, some of them stayed in Titiwungen Selatan. They choose this place because the location is located in central of Manado City. So, they can be easily going to the university around Manado. Beside that, the environment is peaceful and comfortable and the people is friendly and outgoing, that’s make the student can easily interact and adapt. With all of social activity, like social services, social religion activity and the other activity. The student from Tidore can adapt with Manadonese and because of that process start from a good behavior and their capability of adapt, that can create a good Social Adaption. Keywords: adaptation, interaction, student